The Protection of Personal Data and the Exercise of Rights relating to Health Care - Analysis of a Decision of the Constitutional Court of Serbia - Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The Law on the Right to Health Care of Children and Pregnant Women was challenged before the Constitutional Court of Serbia in the part which relating to the obligation of providing specified medical data to the Republic Fund for Health Insurance. The evaluation was requested in relation to Article 42 of the Constitution of the Republic of Serbia as well as in relation to Article 8 of the European Convention on Human Rights and Fundamental Freedoms. The availability of specified health information as a condition of exercising the right to health care of separated categories of the population was considered in the context of alleged violation of the right to protection of personal data and the right to respect for private and family life. In other words, the question which was opened was a matter of collision of two rights that have different legal nature: the right to health care and the right to protection of personal data. The paper analyzes the decisions of the Constitutional Court on the conformity of the disputed provisions with Constitution and ratified international treaty, while the purpose of the analysis pointing to problematic places in the decision as well as the relevant constitutional issues in the decision-making procedure that have not been opened.